Characteristics of electroencephalogram of mother and baby at screening of physical fields - I. A. Belyakova; A. N. Baikov (Бюллетень сибирской медицины, 2012)
Cortex biopotentials of mother and baby have been measured at their physical fields shielded by a folgoizolon screen. The used screened box decreased the infrared field испытуемых by 95% and the acoustic field by 20%. A possible reaction in the form of decrease of alpha rhythm in the sensory cortex was not observed. The dynamics of the EEG amplitude, power, and rhythm frequency during the tests had individual character and was independent of the presence or absence of a screen. The result obtained may be explained by the fact that the 20% decrease of acoustic signals is insufficient for the deprivation reaction of mother and baby для реакции or other sensory modalities are important for them.